Load flow analysis of 10 bus loop distribution network excited by a generator simulated using open modelica - P. Abirami; C. N. Ravi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
In recent days, due to advancement in technology, the end users are facing severe power quality issues. Load flow analysis is one of the fundamental methodologies in solving power network problems. The key importance of Load flow analysis is to improve the performance of distribution network. The main intention of this reserach is to carry out the load flow and voltage stability analysis of 10 bus loop distribution network energized by a generator. Load flow analysis is carried out by using Newton Raphson method. The per unit voltage and angle of the proposed network is determined in all 10 buses by load flow analysis. The voltage stability analysis is implemented by introducing a fault in the network. Here, a power fault is injected at bus 4 between the time interval of 2 to 3 sec to analyse the stability of the system. The voltage stability of the system is analysed for the network with and without automatic voltage regulator (AVR). The AVR unit is tuned by using power system stabilizer (PSS). The results are examined by simulating the network using open modelica connection editor.  From the simulation results the per unit voltages and angles at all 10 buses are determined for the network with and without AVR. By comparing both the results it is proved that the network with AVR has better voltage stability than the other. Thus, the voltage stability of the system is improved by connecting the generator with AVR and PSS.